The Impact of Modern Digital Accounting Technologies and Software on the Future of the Accounting Profession: A Field Study of the Expected Transformations and Challenges - Abdulrazaq Hussen, Noor (Iraqi Journal for Administrative Sciences, 2026)
This study aims to analyze the impact of modern digital accounting technologies and software on the future of the accounting profession and how these tools can contribute to addressing expected professional transformations and challenges. The study relied on a sample of 133 participants, including accountants, auditors, and academics. Data were collected through an electronic questionnaire and analyzed using descriptive methods and linear regression. The results revealed that automating routine accounting processes and integrating digital data with financial reporting systems are the most influential factors in developing the profession and enhancing the quality of professional performance. The findings also indicated that the use of modern accounting software and artificial intelligence technologies constitutes supportive factors that enhance the efficiency of comprehensive digital implementation, with their benefits emerging through the adoption of an integrated digital environment that supports advanced analysis and decision-making. The study recommends enhancing professional training and updating academic curricula in line with digital transformation requirements.